The 2016 Melbourne thunderstorm asthma epidemic: Risk factors for severe attacks requiring hospital admission. Issue 1 (11th October 2018) - Hew, Mark; Lee, Joy; Susanto, Nugroho H.; Prasad, Shivonne; Bardin, Philip G.; Barnes, Sara; Ruane, Laurence; Southcott, Anne M.; Gillman, Andrew; Young, Alan; Rangamuwa, Kanishka; O'Hehir, Robyn E.; et al.
Abstract: Background: The world's most catastrophic and deadly thunderstorm asthma epidemic struck Melbourne, Australia, on November 21, 2016. Objective: Among thunderstorm‐affected patients presenting to emergency rooms (ERs), we investigated risk factors predicting severe attacks requiring admission to hospital. Methods: Thunderstorm‐affected patients were identified from ER records at the eight major Melbourne health services and interviewed by telephone. Risk factors for hospital admission were analyzed. Results: We interviewed 1435/2248 (64%) of thunderstorm‐affected patients, of whom 164 (11.4%) required hospital admission. Overall, rhinitis was present in 87%, and current asthma was present in 28%. Odds for hospital admission were higher with increasing age (odds ratio 1.010, 95% CI 1.002, 1.019) and among individuals with current asthma (adjusted odds ratio [aOR] 1.87, 95% CI 1.26, 2.78). Prior hospitalization for asthma in the previous 12 months further increased the odds for hospital admission (aOR 3.16, 95% CI 1.63, 6.12). Among patients of Asian ethnicity, the odds for hospital admission were lower than for non‐Asian patients (aOR 0.59, 95% CI 0.38, 0.94), but higher if born in Australia (OR = 5.42, 95% CI 1.56, 18.83). Conclusions: In epidemic thunderstorm asthma patients who presented to the ER, higher odds for hospital admission among patients with known asthma were further amplified by recent asthma admission, highlighting the vulnerability conferred by suboptimal disease control. Odds for hospital admission were lower in Asian patients born overseas, but higher in Asian patients born locally, than in non‐Asian patients; these observations suggest susceptibility to severe thunderstorm asthma may be enhanced by gene‐environment interactions. Abstract : We examined patients with acute asthma, who presented to Emergency Rooms during the 2016 Melbourne thunderstorm asthma epidemic. Patients with current asthma had higher odds (1.9) for hospital admission, hospitalization for asthma in the prior 12 months further increased the odds by 3.16. Among patients of Asian ethnicity, odds for hospital admission were lower than for non‐Asian patients (0.59), but higher if born in Australia (5.42), suggesting enhanced susceptibility from gene‐environment interactions.